Digitally Connected, Spiritually Rooted: Mubadalah and The Ethics of Communication In Contemporary Muslim Family in Indonesia - Nurhidayah, Yayah; Gumiandari, Septi; Nafi’a, Ilman; Eti Nurhayati; Firdaus, Slamet (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
Amid the rapid digitalization of everyday life, urban Muslim families in selected Indonesian cities are experiencing a paradox in their communication practices. Digital technologies create new avenues for connection, yet they simultaneously risk weakening affective intimacy and reinforcing patriarchal authority within households. This study examines how digital family communication reflects and challenges traditional power relations through Islamic ethical perspectives, particularly Islamic communication ethics and gender-equitable theology, using the mubadalah approach, which emphasizes mutuality, justice, and compassion in familial relations. Employing a qualitative field research design, the study collected data from 18 informants representing eight Muslim families across Jakarta, Yogyakarta, Cirebon, Bandung, and Makasar through semi-structured in-depth interviews and focus group discussions. Thematic analysis reveals four interrelated dynamics: the shift from physical to digital interaction; the reassertion of patriarchal control through digital devices; the emergence of shared decision-making practices such as shura; and persistent ethical tensions between traditional norms and the transformative possibilities of digital media. The study argues that digital communication in Muslim families is never ethically neutral; it is shaped by spiritual, cultural, and gendered norms. When internalized and practiced in daily interactions, mubadalah values offer a powerful framework for cultivating just, spiritually grounded, and emotionally resilient family relationships in the digital age. These findings highlight the urgency of integrating mubadalah-based ethics into family education programs and gender-sensitive communication pedagogy.